Implementation of autonomous vehicle onto roadways. A step to a Theory of Automated Road Traffic. - Doerr, Heinz; Romstorfer, Andreas (Trialog Publishers, 2020)
At present, automation researchers and automotive component developers perceive the car to be a solitary object that constitutes a sort of singularity, which both triggers and copes with events onto roadways. As far as we know, the setting in which events occur along a road and require automated responses has so far been studied only at a highly abstract level and only for singular events that occur directly in the course of traffic. No comprehensive analysis has so far been attempted that discusses structures of the physical setting in greater detail both objectively and in terms of spatiality and that looks into their disposition for anthropogeneous intervention in response to autonomous vehicle movement.
Keywords: Verkehr; Straßenverkehr; Verkehrsablauf; Fahrzeug; Autonomes Fahren; Straßenraum; Raumaufteilung; Verkehrsnetz; Verkehrsregelung; Verkehrsforschung; Informationsgewinnung; Szenario; Informationsverarbeitung; Verkehrsmanagement